Development of Metro Lampung's Typical Batik Motif: One Pattern Produces Two Motifs on the Front of the Sanggit - Mulyanto Mulyanto; Lili Hartono; Endang Sri Handayani (Mudra Jurnal Seni Budaya, 2026)
Lampung Province has several distinctive motifs that are icons of the Lampung region, such as the siger motif, pepper leaf, tree of life, and ship. Likewise, Metro Regency also has a distinctive regional motif, namely the leluwak motif. The purpose of this study is to develop typical Lampung and Metro batik motifs to be marketed in the Metro Lampung area. The research was conducted using a qualitative approach, literature study, and participatory action studies by batik entrepreneurs and craftsmen in the DR Sragen batik business, Central Java, and Metro Lampung. Data sources used include literature on Lampung and Metro motifs, informants from the Lampung community leaders, batik entrepreneurs and craftsmen, and the community using batik products. Research data were collected through literature study techniques, observation, interviews, focused discussions, motif design creation actions, batik production process actions, and batik product testing by consumers. Data were analyzed using interactive models and consumer tests. The research produced one master design of a typical Metro batik motif. Furthermore, the design was produced in 5 batik products with different color compositions. The resulting batik cloth was made using a printing technique measuring 115cm x 240cm. From one resulting motif design, it can be made into clothing (long-sleeved shirt or skirt) with two different motifs and a front view. The sanggit motif of the front shirt lies in the 25cm master motif and the 60cm motif. Of the five different color compositions, the most popular color composition among Metro residents is the red-green batik composition, and the least popular composition is the brown-blue composition.